Mechanism for ginsenoside Rh2-induced apoptosis of triple-negative breast cancer MDA-MB-231 cells - Y. Zeng; J. Mao; X. Wang; B. Yin; Z. Shen; C. Di; W. Gu; M. Wu (IMR Press, 2020)
Objective: The authors aimed to explore the apoptosis of triple-negative breast cancer (TNBC) MDA-MB-231 cells induced by ginsenoside Rh2 and the underlying mechanism. Materials and Methods: Changes in the viability of MDA-MB-231 cells after treatment with 20 (S)-Rh2 and 20 (R)-Rh2 for 48 hours were detected by MTT assay. Changes in the morphology of cell nuclei were observed by DAPI staining. The expressions of caspase-3, caspase-9, cytochrome c, Smac, Bak, and Bax related to the mitochondrial pathway were detected by Western blotting. Results: 20 (S)-Rh2 inhibited the proliferation of MDA-MB-231 cells, but 20 (R)-Rh2 failed to do so. After treatment with 20(S)-Rh2 for two hours under visible light, they shrank and had incomplete morphology, whereas the morphology of control group hardly changed. Under UV light, the nuclei stained with DAPI were blue. After treatment with 20 (S)-Rh2 for one hour, the nuclei shrank and ruptured, and nearly 90% ruptured at two hours. In contrast, the nuclei of PBS control group remained intact. The activity of caspase-9 in MDA-MB-231 cells treated with 7.5 µg/mL 20 (S)-Rh2 was increased at 30 minutes, and gradually increased over extended time. Under identical conditions, the activity of caspase-9 in control group did not change significantly. Cytochrome c and Smac were released from mitochondria to the cytoplasm at one hour after treatment with 7.5 µg/mL 20 (S)-Rh2. However, such release was not detected in the control group. Bax was translocated after 30 minutes of treatment with 7.5 µg/mL 20 (S)-Rh2, which then gradually accumulated in mitochondria over time and peaked at two hours. The Bax expression in the entire cell lysate remained unchanged. The translocation of Bax was not detected in control group. Conclusion: 20 (S)-Rh2 evidently inhibited the proliferation of TNBC cell line MDA-MB-231. It killed the cells by inducing apoptosis, probably by activating the mitochondrial pathway.